Thermo-oxidative aging resistant regenerated polypropylene fiber and preparation method thereof

CN122879846APending Publication Date: 2026-10-09HUBEI BOTAO SYNTHETIC FIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610761894.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的是针对现有技术中再生丙纶纤维因聚丙烯分子结构对热、氧敏感,易发生热氧老化而导致性能下降、使用寿命短的问题,提供一种抗热氧老化的再生丙纶纤维及其制备方法

Benefits of technology

1.本发明通过核壳型受阻酚缓释主抗氧剂与辅抗氧剂协同作用,能够持续捕捉热氧老化过程中产生的自由基,并分解老化过程中形成的氢过氧化物,从而有效抑制聚丙烯分子链断裂和氧化降解,使再生丙纶纤维在热氧老化后仍保持较好的力学性能稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879846A_ABST
    Figure CN122879846A_ABST
Patent Text Reader

Abstract

The application discloses a heat-oxygen-aging-resistant regenerated polypropylene fiber and a preparation method thereof, and relates to the technical field of high polymer materials. The heat-oxygen-aging-resistant regenerated polypropylene fiber is prepared from the following raw materials in parts by mass: 80-90 parts of regenerated polypropylene particles, 0.7-1.0 parts of a main antioxidant, 1.0-1.2 parts of an auxiliary antioxidant, 0.4-0.7 parts of a light stabilizer, 0.3-0.6 parts of a lubricant and 0.4-0.8 parts of a nucleating agent. Through the synergistic effect of the specific main antioxidant and the auxiliary antioxidant, the thermal oxygen degradation of the polypropylene molecular chain is effectively inhibited, the regenerated polypropylene fiber can still maintain a relatively high breaking strength and elongation at break after heat-oxygen aging, and the defects of traditional regenerated polypropylene fibers, such as easy aging and embrittlement and rapid decay of mechanical properties, are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a regenerated polypropylene fiber resistant to thermo-oxidative aging and its preparation method. Background Technology

[0002] Polypropylene fiber, commonly known as polypropylene fiber, is widely used due to its advantages such as light weight, high strength, and resistance to chemical corrosion. The recycling and reuse of waste plastic products, especially waste polypropylene products, to produce recycled polypropylene fiber has become an important direction for resource recycling and reducing environmental pollution.

[0003] However, polypropylene molecules contain a large number of tertiary carbon atoms, making them highly sensitive to heat and oxygen. During processing and use, they are prone to thermo-oxidative aging, leading to molecular chain breakage and degradation. This results in a significant decrease in the material's mechanical properties, yellowing, and shortened service life. This problem is particularly pronounced when using recycled materials, as they may have already been exposed to heat, light, and oxygen during their previous lifespan, partially disrupting their molecular weight and stabilization system, thus exhibiting even worse thermo-oxidative aging stability. Traditional virgin polypropylene fibers or simply recycled polypropylene fibers often fail to meet the durability requirements of applications.

[0004] Therefore, developing a formulation and preparation method that can effectively inhibit the thermo-oxidative aging process and significantly improve the thermal stability and service life of recycled polypropylene fibers is of great significance for promoting the high-value recycling and utilization of polypropylene and expanding the application fields of recycled polypropylene. Summary of the Invention

[0005] The purpose of this invention is to address the problem in existing technologies where recycled polypropylene fibers are prone to thermal and oxygen aging due to the sensitivity of the polypropylene molecular structure to heat and oxygen, resulting in performance degradation and short service life. This invention provides a recycled polypropylene fiber resistant to thermal and oxygen aging and its preparation method. Through a specific composite stabilization system and process, this fiber significantly improves the thermal and oxygen stability of recycled polypropylene, thereby expanding its applications in fields requiring high durability.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A type of regenerated polypropylene fiber resistant to heat and oxygen aging is composed of the following raw materials in parts by weight: 80-90 parts of regenerated polypropylene granules, 0.7-1.0 parts of primary antioxidant, 1.0-1.2 parts of secondary antioxidant, 0.4-0.7 parts of light stabilizer, 0.3-0.6 parts of lubricant, and 0.4-0.8 parts of nucleating agent.

[0007] The main antioxidant is composed of the following raw materials in parts by weight: 100 parts mesoporous silica, 35-55 parts antioxidant 1010, 10-25 parts antioxidant 1076, 8-15 parts γ-glycidyl etheroxypropyltrimethoxysilane, 5-12 parts 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 12-25 parts maleic anhydride-grafted polypropylene wax, 200-350 parts anhydrous ethanol, 240-360 parts ethyl acetate, and 0.5-1.5 parts glacial acetic acid.

[0008] Furthermore, the auxiliary antioxidant is one or more of antioxidant 168 and antioxidant 626.

[0009] Furthermore, the light stabilizer is one or more of light stabilizers 770, UV-32, and UV-326.

[0010] Furthermore, the preparation method of the primary antioxidant includes the following steps: S1. Pretreatment of mesoporous silica: The mesoporous silica nanospheres were placed in a forced-air drying oven and dried at 110°C for 4 hours to remove the adsorbed water in the pores and obtain pretreated mesoporous silica nanospheres. S2. Hindered phenolic antioxidant channel loading: Antioxidant 1010 and antioxidant 1076 were added to ethyl acetate and stirred at 55°C until completely dissolved to obtain a hindered phenolic antioxidant solution; pretreated mesoporous silica nanospheres were added to the hindered phenolic antioxidant solution and kept under a vacuum of -0.08 MPa for 40 min, then restored to normal pressure and stirred for 2 h to allow the hindered phenolic antioxidant to enter the mesoporous silica channels; subsequently, ethyl acetate was removed under reduced pressure at 45°C to obtain hindered phenol-loaded mesoporous silica; S3. Construction of silane cross-linked shell: Hindered phenol-supported mesoporous silica was dispersed in anhydrous ethanol, γ-glycidyl etheroxypropyltrimethoxysilane and glacial acetic acid were added, and the mixture was stirred at 65°C for 5 h. After the reaction was completed, the mixture was filtered, washed with ethanol, and dried under vacuum at 60°C to obtain epoxy silane-coated particles. S4. Hindered phenolic group interface fixation: Epoxy silane-coated particles were added to ethyl acetate, and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid was added. The mixture was stirred at 80°C for 4 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain hindered phenol-modified core-shell particles. S5. Polypropylene compatible shell coating: Maleic anhydride-grafted polypropylene wax is heated to 120°C to melt, and hindered phenol-modified core-shell particles are added to it. The mixture is stirred at 800 r / min for 30 min to uniformly coat the surface of the particles with maleic anhydride-grafted polypropylene wax. After cooling, the mixture is pulverized and passed through a 300-mesh sieve to obtain the core-shell type hindered phenol slow-release main antioxidant.

[0011] Furthermore, the lubricant is one or more of zinc stearate, calcium stearate, polyethylene wax, and ethylene bis-stearamide.

[0012] Furthermore, the nucleating agent is one or more of dimethyl dibenzylidene sorbitol, talc, and calcium carbonate.

[0013] Furthermore, the primary antioxidant can also be used in the preparation of ultra-high molecular weight polyethylene fiber, aramid, and polyester.

[0014] A method for preparing regenerated polypropylene fiber resistant to heat and oxygen aging includes the following steps: A1. Raw material pretreatment: The recycled polypropylene granules are dried at a constant temperature for 3-5 hours to remove moisture from the granules and then cooled to room temperature for later use. A2. High-speed mixing: The dried recycled polypropylene granules, main antioxidant, auxiliary antioxidant, light stabilizer, lubricant and nucleating agent are put into a high-speed mixer. First, the mixture is premixed at low speed for 3-5 minutes, and then heated to 60-70℃ and stirred at high speed for 8-12 minutes to obtain a uniform blend. A3. Melt extrusion plasticizing: The homogeneous blended material is fed into a twin-screw extruder for melt extrusion. The temperature settings for each zone of the extruder are: Zone 1 190-200℃, Zone 2 200-210℃, Zone 3 210-220℃, and Die head 215-225℃. The screw speed is controlled at 180-220 r / min. After melting and homogenization, impurities are removed by filtration to obtain the molten melt. A4. Spinning and drawing: The molten melt is conveyed to the spinneret of the spinning assembly by a metering pump under stable pressure and extruded to form nascent fibers. The spinning temperature is 215-230℃, the cooling air temperature is 20-25℃ and the air speed is 0.8-1.2m / s. The nascent fibers are cooled and shaped by side blowing air. Then, they are drawn by multi-stage hot rollers. The total draw ratio is controlled at 3.0-4.5 times and the hot roller temperature is 75-90℃ to obtain the drawn fibers. A5. Setting and winding: The stretched fiber is heat-set, oiled evenly, and finally wound up to obtain a finished product, a regenerated polypropylene fiber resistant to heat and oxygen aging.

[0015] Furthermore, the constant temperature drying in step A1 is performed using a hot air dryer at a temperature of 80-90℃.

[0016] Furthermore, in step A2, the stirring speed of the high-speed mixer is 150-200 r / min in the low-speed range and 800-1000 r / min in the high-speed range.

[0017] Furthermore, in step A3, the vacuum level of the twin-screw extruder is maintained at -0.07 to -0.09 MPa.

[0018] Furthermore, in step A5, the heat setting temperature is 95-110℃, and the heat setting time is 15-25s; the fiber oiling uses a polypropylene-specific oiling agent, and the amount of oiling agent is controlled at 0.3%-0.6%.

[0019] This invention uses recycled polypropylene granules as a matrix and constructs a composite stable protection system integrating processing and service life through the synergistic effect of a primary antioxidant, secondary antioxidant, light stabilizer, lubricant, and nucleating agent. Specifically, the primary antioxidant is loaded with antioxidants 1010 and 1076 via mesoporous silica, and forms a silane cross-linked shell with γ-glycidoxypropyltrimethoxysilane. Then, hindered phenolic groups are introduced using 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid. Finally, a polypropylene-compatible outer shell is formed by grafting maleic anhydride onto polypropylene wax, enabling the core-shell type hindered phenolic slow-release primary antioxidant. This process achieves uniform dispersion and slow release of hindered phenolic active components within recycled polypropylene granules, continuously capturing free radicals generated during thermo-oxidative aging and terminating the chain reaction of polypropylene molecular chain oxidative degradation. An auxiliary antioxidant further decomposes hydroperoxides generated during aging, reducing free radical regeneration. A light stabilizer inhibits light-induced oxidative aging, forming a complementary protection with the thermo-oxidative stabilization system. A lubricant improves processing fluidity during melt extrusion plasticization and spinning drawing, reducing shear heat generation and processing degradation. A nucleating agent promotes polypropylene crystal refinement and structural densification, enhancing the fiber's physical barrier against oxygen and heat intrusion. Thus, the components synergistically enhance free radical capture, peroxide decomposition, photo-oxidative protection, processing loss reduction, and crystal structure regulation, resulting in a thermo-oxidative resistant recycled polypropylene fiber that maintains good breaking strength, elongation, and appearance stability even after thermo-oxidative aging.

[0020] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes the synergistic effect of a core-shell type hindered phenolic slow-release primary antioxidant and a secondary antioxidant to continuously capture free radicals generated during thermo-oxidative aging and decompose hydroperoxides formed during aging. This effectively inhibits polypropylene molecular chain breakage and oxidative degradation, allowing regenerated polypropylene fibers to maintain good mechanical property stability after thermo-oxidative aging.

[0021] 2. This invention introduces a light stabilizer, which forms a composite stabilization system with the primary antioxidant and the secondary antioxidant. This system can not only inhibit the performance degradation caused by thermo-oxidation, but also reduce the impact of the photo-oxidation environment on the fiber color. This makes the recycled polypropylene fiber less prone to obvious yellowing, brittleness and appearance degradation after aging, thus improving the problems of easy discoloration and easy aging of traditional recycled polypropylene fiber.

[0022] 3. This invention forms a polypropylene compatible shell by grafting maleic anhydride onto polypropylene wax, which improves the dispersibility and compatibility of the main antioxidant in recycled polypropylene particles. At the same time, the lubricant reduces shear heat generation during melt extrusion plasticization and spinning drawing, and the nucleating agent promotes the refinement of polypropylene crystals and the densification of the structure, so that the resulting recycled polypropylene fiber, which is resistant to heat and oxygen aging, has good processing stability, structural stability and long-term durability. Attached Figure Description

[0023] Figure 1 This is a SEM image of the main antioxidant 1 prepared in this invention.

[0024] Figure 2 XPS image of the main antioxidant 1 prepared in this invention. Detailed Implementation

[0025] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Preparation Example 1 Preparation of primary antioxidant 1: 1. Raw material weight parts: 100 parts of mesoporous silica nanospheres, 45 parts of antioxidant 1010, 18 parts of antioxidant 1076, 12 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 8 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 18 parts of maleic anhydride-grafted polypropylene wax, 280 parts of anhydrous ethanol, 170 parts of ethyl acetate, and 1.0 part of glacial acetic acid.

[0027] The mesoporous silica nanospheres were purchased from Shanghai McLean Biochemical Technology Co., Ltd., M697868.

[0028] The maleic anhydride-grafted polypropylene wax was purchased from Foshan Weng Kai'er Trading Co., Ltd. ® 630R.

[0029] 2. Preparation method: S1. Pretreatment of mesoporous silica: Weigh 100 parts of mesoporous silica nanospheres, spread them evenly in a stainless steel tray, control the thickness of the material layer to be 8 mm, place them in a forced-air drying oven, and dry them at 110℃ for 4 h to remove adsorbed water and surface free water in the pores of the mesoporous silica nanospheres; after drying, transfer them to a desiccator to cool to room temperature to obtain pretreated mesoporous silica nanospheres.

[0030] S2. Hindered phenolic antioxidant pore loading: Weigh 45 parts of antioxidant 1010 and 18 parts of antioxidant 1076, add them to 170 parts of ethyl acetate, and stir at 400 r / min for 40 min at 55 °C to completely dissolve antioxidant 1010 and antioxidant 1076, obtaining a hindered phenolic antioxidant solution; then add the pretreated mesoporous silica nanospheres obtained in step S1 to the hindered phenolic antioxidant solution, and stir and disperse at 500 r / min for 30 min, then... The system was placed in a vacuum impregnation apparatus and kept under a vacuum of -0.08 MPa for 40 min to allow the hindered phenol antioxidant solution to fully enter the pores of the mesoporous silica nanospheres. Then, the pressure was restored to normal and the mixture was stirred at 55 °C for 2 h to further load antioxidants 1010 and 1076 into the pores of the mesoporous silica nanospheres. After the reaction was completed, ethyl acetate was removed under reduced pressure at 45 °C and -0.09 MPa to obtain hindered phenol-loaded mesoporous silica.

[0031] S3. Construction of silane cross-linked shell: The hindered phenol-supported mesoporous silica obtained in step S2 was added to 280 parts of anhydrous ethanol and stirred and dispersed at 600 r / min for 20 min. Then, 12 parts of γ-glycidoxypropyltrimethoxysilane and 1.0 part of glacial acetic acid were added, and the temperature was raised to 65℃. The reaction was carried out under nitrogen protection and stirred at 500 r / min for 5 h to allow γ-glycidoxypropyltrimethoxysilane to condense and form an epoxy-containing silane cross-linked shell on the surface of the mesoporous silica. After the reaction was completed, the reaction solution was cooled to room temperature and filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm. The filter cake was washed three times with anhydrous ethanol, with 80 parts of anhydrous ethanol used for each wash. The filter cake was then placed in a vacuum drying oven and dried at 60℃ and -0.08 MPa for 8 h to obtain epoxy silane-coated particles.

[0032] S4. Fixation of hindered phenolic groups at the interface: The epoxy silane-coated particles obtained in step S3 were added back into 120 parts of ethyl acetate and stirred and dispersed at 500 r / min for 20 min. Then, 8 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid were added, and the mixture was heated to 80℃ and stirred for 4 h under nitrogen protection. This allowed the carboxyl groups in 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to undergo a ring-opening reaction with the epoxy groups on the surface of the epoxy silane-coated particles, thereby fixing the hindered phenolic structure at the particle interface. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed sequentially with ethyl acetate and anhydrous ethanol, with ethyl acetate washing twice and anhydrous ethanol washing twice, each time using 60 parts of washing solution. The washed filter cake was placed in a vacuum drying oven and dried at 60℃ and -0.08 MPa for 10 h to obtain hindered phenol-modified core-shell particles.

[0033] S5. Polypropylene Compatible Shell Coating: Weigh 18 parts of maleic anhydride-grafted polypropylene wax and add it to a melt coating vessel equipped with mechanical stirring. Heat the vessel to 120°C and maintain the temperature for 20 minutes to allow it to melt completely. Then, slowly add the hindered phenol-modified core-shell particles obtained in step S4 to the molten maleic anhydride-grafted polypropylene wax, controlling the feeding time to 10 minutes. During the feeding process, maintain the system temperature at 120°C and stir at 800 r / min. After the feeding is completed, continue stirring for 30 minutes to ensure that the maleic anhydride-grafted polypropylene wax uniformly coats the surface of the hindered phenol-modified core-shell particles, forming a polypropylene compatible shell. After the reaction is completed, pour the material into a clean stainless steel tray and allow it to cool naturally to room temperature. After pulverizing the material, pass it through a 300-mesh sieve and collect the sieve residue to obtain the main antioxidant 1.

[0034] SEM image of primary antioxidant 1, as shown Figure 1 As shown, the main antioxidant 1 exhibits a near-spherical or semi-spherical particle morphology with relatively clear particle boundaries. The surface shows a certain degree of roughness and fine protrusions, indicating that after being loaded with antioxidants 1010 and 1076, the mesoporous silica nanospheres form a silane cross-linked shell and a maleic anhydride-grafted polypropylene wax compatible shell on their surface. This transforms the original smooth inorganic surface into a rough interface with organic coating characteristics. Slight particle agglomeration is observed, but no large-area caking or severe hard agglomeration is seen. This morphology facilitates better dispersion of the main antioxidant 1 in the recycled polypropylene melt and reduces spinneret clogging, fiber breakage, and localized stress concentration problems caused by large particle agglomeration during spinning.

[0035] XPS plot of primary antioxidant 1, as shown Figure 2 As shown, the XPS full spectrum of the main antioxidant 1 reveals characteristic peaks of C1s, O1s, Si2s, and Si2p. The C1s peak has the highest intensity, indicating that the surface of the main antioxidant 1 is rich in organic carbon components, originating from antioxidants 1010 and 1076, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, and a compatible shell of maleic anhydride-grafted polypropylene wax. The O1s peak mainly corresponds to mesoporous silica, silane cross-linked shells, and oxygen-containing functional groups such as ester groups, carboxyl groups, and ether bonds. The presence of Si2s and Si2p peaks indicates that the sample retains the mesoporous silica framework and the silicon-oxygen structure introduced by γ-glycidoxypropyltrimethoxysilane. The weak signals of Na1s, NaKLL, and Cl2p in the spectrum can be attributed to trace amounts of inorganic impurities and background signals remaining during sample preparation, washing, or testing. Their peak intensities are low and do not affect the judgment that the main antioxidant 1 is composed primarily of C, O, and Si. The above results indicate that the main antioxidant 1 has formed a composite core-shell structure with mesoporous silica as the inorganic core, organic antioxidant components, and a polypropylene compatible shell.

[0036] Comparative Preparation Example 1 The preparation of a primary antioxidant 2 is carried out by referring to the preparation method of Preparation Example 1, except that the mesoporous silica nanospheres are replaced with ordinary nano silica of equal mass, and the rest is the same as in Preparation Example 1.

[0037] Comparative Preparation Example 2 The preparation of a primary antioxidant 3 is carried out by referring to the preparation method of Preparation Example 1, except that antioxidant 1076 is replaced with an equal mass of antioxidant 1010, and the rest is the same as in Preparation Example 1.

[0038] Comparative preparation example 3 The preparation of a primary antioxidant 4 is carried out by referring to the preparation method of Preparation Example 1, except that the γ-glycidoxypropyltrimethoxysilane is replaced with an equal mass of methyltrimethoxysilane, and the rest is the same as in Preparation Example 1.

[0039] Comparative preparation example 4 The preparation of a primary antioxidant 5 is carried out by referring to the preparation method of Preparation Example 1, except that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is replaced with an equal mass of benzoic acid, and the rest is the same as in Preparation Example 1.

[0040] Comparative preparation example 5 The preparation of a primary antioxidant 6 is carried out by referring to the preparation method of Preparation Example 1, except that the maleic anhydride-grafted polypropylene wax is replaced with an equal mass of polypropylene wax, and the rest is the same as in Preparation Example 1.

[0041] Comparative preparation example 6 The preparation of a primary antioxidant 7 is carried out by referring to the preparation method of Preparation Example 1, except that antioxidant 1010 is replaced with an equal mass of antioxidant 1076, and the rest is the same as in Preparation Example 1.

[0042] Comparative preparation example 7 The preparation of a primary antioxidant 8 was carried out by referring to the preparation method of Preparation Example 1, except that the glacial acetic acid was replaced with an equal mass of deionized water, and the rest remained the same as in Preparation Example 1.

[0043] Comparative Preparation Example 8 The preparation of a primary antioxidant 9 was carried out by referring to the preparation method of Preparation Example 1, except that the ethyl acetate was replaced with an equal mass of anhydrous ethanol, and the rest remained the same as in Preparation Example 1.

[0044] Example 1 Preparation of a regenerated polypropylene fiber resistant to heat and oxygen aging: 1. Raw material weight parts: Recycled polypropylene granules: 85 parts, selected from white PP coating and drawing material, purchased from: Dongguan Shengxin New Material Technology Co., Ltd.; Primary antioxidant: 0.9 parts, using primary antioxidant 1 prepared in Preparation Example 1; Co-antioxidant: 1.1 parts, antioxidant 168 is selected; Light stabilizer: 0.5 parts, light stabilizer 770 is selected; Lubricant: 0.4 parts, zinc stearate is preferred; Nucleating agent: 0.6 parts, dimethyl dibenzylidene sorbitol is selected.

[0045] 2. Preparation method: A1. Raw material pretreatment: Place the recycled polypropylene granules into a hot air dryer and dry them at a constant temperature of 85℃ for 4 hours to fully remove the internal moisture of the granules. After cooling to room temperature, they are ready for use. A2. High-speed mixing: Weigh the dried recycled polypropylene granules, main antioxidant, auxiliary antioxidant, light stabilizer, lubricant, and nucleating agent, and put them into a high-speed mixer; first, stir at a low speed of 180 r / min for 4 min to complete the premixing, then heat to 65℃ and stir at a high speed of 900 r / min for 10 min to obtain a uniform blend. A3. Melt extrusion plasticizing: The homogeneous blended material is fed into a twin-screw extruder. The temperature of the extruder is 195℃ in zone 1, 205℃ in zone 2, 215℃ in zone 3, and 220℃ at the die head. The screw speed is 200 r / min, and the vacuum degree is maintained at -0.08 MPa. After the material is melted and homogenized, it is filtered through a filter screen to remove impurities and obtain a clean melt. A4. Spinning and drawing: The molten melt is conveyed to the spinning assembly by a metering pump under stable pressure, and is extruded by the spinneret to form nascent fibers. The spinning temperature is 220℃. The nascent fibers are cooled and shaped by side blowing air at 22℃ and a wind speed of 1.0m / s. Then, the fibers are drawn by multi-stage hot rollers with a total draw ratio of 4 times and a hot roller temperature of 82℃. A5. Setting and winding: The stretched fiber is heat-set at 102℃ for 20 seconds; a special polypropylene oil is applied, and the amount of oil adhering is controlled at 0.45%; after equalization treatment, it is wound up to obtain a finished product, a regenerated polypropylene fiber resistant to heat and oxygen aging.

[0046] Example 2 The preparation of a regenerated polypropylene fiber resistant to thermo-oxidative aging is carried out by referring to the preparation method in Example 1, except that the mass fractions of the raw materials are replaced, while the rest remains the same as in Example 1. The specific mass fractions of the raw materials are as follows: Recycled polypropylene granules: 80 parts; Main antioxidant: 0.7 parts; Co-antioxidant: 1.0 part; Light stabilizer: 0.4 parts; Lubricant: 0.3 parts; Nucleating agent: 0.4 parts.

[0047] Example 3 The preparation of a regenerated polypropylene fiber resistant to thermo-oxidative aging is carried out by referring to the preparation method in Example 1, except that the mass fractions of the raw materials are replaced, while the rest remains the same as in Example 1. The specific mass fractions of the raw materials are as follows: Recycled polypropylene granules: 90 parts; Main antioxidant: 1.0 part; Co-antioxidant: 1.2 parts; Light stabilizer: 0.7 parts; Lubricant: 0.6 parts; Nucleating agent: 0.8 parts.

[0048] Comparative Examples 1-8 The preparation of a regenerated polypropylene fiber resistant to thermo-oxidative aging was carried out by referring to the preparation method in Example 1, except that the main antioxidant was replaced with the main antioxidant 2-9 prepared in Comparative Preparation Examples 1-8, and the rest remained the same as in Example 1.

[0049] Comparative Example 9 The preparation of a regenerated polypropylene fiber resistant to thermo-oxidative aging is carried out by referring to the preparation method in Example 1, except that the main antioxidant is replaced with antioxidant 1010, and the rest is the same as in Example 1.

[0050] Comparative Example 10 The preparation of a regenerated polypropylene fiber resistant to thermo-oxidative aging is carried out according to the preparation method in Example 1, except that the main antioxidant is not added, and the rest is the same as in Example 1.

[0051] Comparative Example 11 The preparation of a regenerated polypropylene fiber resistant to thermo-oxidative aging is carried out according to the preparation method in Example 1, except that the auxiliary antioxidant is not added, and the rest is the same as in Example 1.

[0052] Performance testing 1. Accelerated aging test: In accordance with GB / T7141-2008 and SH / T1542-1993 standards, the polypropylene fibers prepared in the examples and comparative examples were placed in an aging test chamber and the aging conditions were set as follows: 135℃, aging time 96h. After the time was reached, the fibers were taken out and conditioned under standard conditions for 3h before testing.

[0053] 2. Tensile property test: According to GB / T14344-2022 standard, the breaking strength and elongation at break of the polypropylene fibers prepared in the examples and comparative examples were tested, as well as the breaking strength and elongation at break of the samples after the above aging. Calculation: Pre-aging fracture strength = Pre-aging fracture strength / linear density; Strength retention rate = (fracture strength after aging / fracture strength before aging) × 100%; Elongation retention rate = (elongation at break after aging / elongation at break before aging) × 100%, the structure is shown in Table 1.

[0054] 3. Appearance before and after aging: The fiber color, yellowing, brittleness, fuzz, and adhesion were compared before and after aging. The results are shown in Table 1.

[0055] Table 1. Performance test results of the examples and comparative examples

[0056] As shown in Table 1, all examples exhibited good mechanical stability and appearance retention before and after aging. Among them, Example 1 showed the best overall performance, indicating that a relatively sufficient synergistic effect was formed among the main antioxidant, auxiliary antioxidant, light stabilizer, lubricant, and nucleating agent. From a mechanistic perspective, the core-shell hindered phenol slow-release main antioxidant can achieve stable dispersion and continuous release of antioxidant active components by relying on the mesoporous silica channel loading and silane cross-linked shell. The hindered phenol structure can capture free radicals generated during thermo-oxidative aging and inhibit polypropylene molecular chain breakage. The auxiliary antioxidant further decomposes hydrogen peroxide and reduces free radical regeneration. Therefore, the examples showed significantly better retention of fracture strength and elongation at break after aging than the comparative examples. In the comparative examples, when the mesoporous silica, the 1010 / 1076 antioxidant compound system, the silane cross-linked shell, the interface-fixed hindered phenolic groups, or the maleic anhydride-grafted polypropylene wax compatible shell were replaced, the pore loading, interfacial bonding, slow-release capacity, and polypropylene matrix compatibility of the main antioxidant were all weakened. This led to easy migration and aggregation of the antioxidant, or discontinuous antioxidant effects, making the fibers more prone to yellowing, hardening, fuzzing, and brittleness under thermo-oxidative conditions. Without the addition of a main antioxidant or an auxiliary antioxidant, the stabilization system was incomplete, and the free radical capture and peroxide decomposition processes could not be effectively linked, resulting in the most significant thermo-oxidative degradation. In summary, this invention improves the thermo-oxidative aging resistance and post-aging structural integrity of recycled polypropylene fibers through the synergistic antioxidant effect of the core-shell hindered phenolic slow-release main antioxidant and the auxiliary antioxidant, the supplementary protection of the light stabilizer, the processing loss reduction of the lubricant, and the crystallization refinement effect of the nucleating agent.

[0057] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A regenerated polypropylene fiber resistant to thermo-oxidative aging, characterized in that, It is composed of the following raw materials in parts by weight: 80-90 parts recycled polypropylene granules, 0.7-1.0 parts primary antioxidant, 1.0-1.2 parts secondary antioxidant, 0.4-0.7 parts light stabilizer, 0.3-0.6 parts lubricant, and 0.4-0.8 parts nucleating agent; The main antioxidant is composed of the following raw materials in parts by weight: 100 parts mesoporous silica, 35-55 parts antioxidant 1010, 10-25 parts antioxidant 1076, 8-15 parts γ-glycidyl etheroxypropyltrimethoxysilane, 5-12 parts 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 12-25 parts maleic anhydride-grafted polypropylene wax, 200-350 parts anhydrous ethanol, 240-360 parts ethyl acetate, and 0.5-1.5 parts glacial acetic acid.

2. The regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 1, characterized in that, The auxiliary antioxidant is one or more of antioxidant 168 and antioxidant 626; The light stabilizer is one or more of light stabilizers 770, UV-32, and UV-326.

3. The regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 1, characterized in that, The preparation method of the primary antioxidant includes the following steps: S1. Pretreatment of mesoporous silica: The mesoporous silica nanospheres were placed in a forced-air drying oven and dried at 110°C for 4 hours to remove the adsorbed water in the pores and obtain pretreated mesoporous silica nanospheres. S2. Hindered phenolic antioxidant channel loading: Antioxidant 1010 and antioxidant 1076 were added to ethyl acetate and stirred at 55°C until completely dissolved to obtain a hindered phenolic antioxidant solution; pretreated mesoporous silica nanospheres were added to the hindered phenolic antioxidant solution and kept under a vacuum of -0.08 MPa for 40 min, then restored to normal pressure and stirred for 2 h to allow the hindered phenolic antioxidant to enter the mesoporous silica channels; subsequently, ethyl acetate was removed under reduced pressure at 45°C to obtain hindered phenol-loaded mesoporous silica; S3. Construction of silane cross-linked shell: Hindered phenol-supported mesoporous silica was dispersed in anhydrous ethanol, γ-glycidyl etheroxypropyltrimethoxysilane and glacial acetic acid were added, and the mixture was stirred at 65°C for 5 h. After the reaction was completed, the mixture was filtered, washed with ethanol, and dried under vacuum at 60°C to obtain epoxy silane-coated particles. S4. Hindered phenolic group interface fixation: Epoxy silane-coated particles were added to ethyl acetate, and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid was added. The mixture was stirred at 80°C for 4 hours. After the reaction was completed, the mixture was filtered, washed and dried to obtain hindered phenol-modified core-shell particles. S5. Polypropylene compatible shell coating: Maleic anhydride-grafted polypropylene wax is heated to 120°C to melt, and hindered phenol-modified core-shell particles are added to it. The mixture is stirred at 800 r / min for 30 min to uniformly coat the surface of the particles with maleic anhydride-grafted polypropylene wax. After cooling, the mixture is pulverized and passed through a 300-mesh sieve to obtain the core-shell type hindered phenol slow-release main antioxidant.

4. The regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 1, characterized in that, The lubricant is one or more of zinc stearate, calcium stearate, polyethylene wax, and ethylene bis-stearamide.

5. The regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 1, characterized in that, The nucleating agent is one or more of dimethyl dibenzylidene sorbitol, talc, and calcium carbonate.

6. A method for preparing a thermo-oxidative aging resistant regenerated polypropylene fiber according to any one of claims 1-5, characterized in that, Includes the following steps: A1. Raw material pretreatment: The recycled polypropylene granules are dried at a constant temperature for 3-5 hours to remove moisture from the granules and then cooled to room temperature for later use. A2. High-speed mixing: The dried recycled polypropylene granules, main antioxidant, auxiliary antioxidant, light stabilizer, lubricant and nucleating agent are put into a high-speed mixer. First, the mixture is premixed at low speed for 3-5 minutes, and then heated to 60-70℃ and stirred at high speed for 8-12 minutes to obtain a uniform blend. A3. Melt extrusion plasticizing: The homogeneous blended material is fed into a twin-screw extruder for melt extrusion. The temperature settings for each zone of the extruder are: Zone 1 190-200℃, Zone 2 200-210℃, Zone 3 210-220℃, and Die head 215-225℃. The screw speed is controlled at 180-220 r / min. After melting and homogenization, impurities are removed by filtration to obtain the molten melt. A4. Spinning and drawing: The molten melt is conveyed to the spinneret of the spinning assembly by a metering pump under stable pressure and extruded to form nascent fibers. The spinning temperature is 215-230℃, the cooling air temperature is 20-25℃ and the air speed is 0.8-1.2m / s. The nascent fibers are cooled and shaped by side blowing air. Then, they are drawn by multi-stage hot rollers. The total draw ratio is controlled at 3.0-4.5 times and the hot roller temperature is 75-90℃ to obtain the drawn fibers. A5. Setting and winding: The stretched fiber is heat-set, oiled evenly, and finally wound up to obtain a finished product, a regenerated polypropylene fiber resistant to heat and oxygen aging.

7. The method for preparing regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 6, characterized in that, In step A1, the constant temperature drying is performed using a hot air dryer at a temperature of 80-90℃.

8. The method for preparing regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 6, characterized in that, In step A2, the stirring speed of the high-speed mixer is 150-200 r / min in the low-speed range and 800-1000 r / min in the high-speed range.

9. The method for preparing regenerated polypropylene fiber resistant to thermo-oxidative aging according to claim 6, characterized in that, In step A3, the vacuum level of the twin-screw extruder is maintained between -0.07 and -0.09 MPa.

10. The method for preparing a thermo-oxidative aging resistant recycled polypropylene fiber according to claim 6, characterized in that, In step A5, the heat setting temperature is 95-110℃, and the heat setting time is 15-25s; the fiber oiling uses a special polypropylene oiling agent, and the amount of oiling agent is controlled at 0.3%-0.6%.